2018
DOI: 10.1155/2018/3428303
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable Water Vapor Retrieval and Analysis by Multiple Data Sources: Ground-Based GNSS, Radio Occultation, Radiosonde, Microwave Satellite, and NWP Reanalysis Data

Abstract: Precipitable water vapor (PWV) content detection is vital to heavy rain prediction; up to now, lots of different measuring methods and devices are developed to observe PWV. In general, these methods can be divided into two categories, ground-based or space-based. In this study, we analyze the advantages and disadvantages of these technologies, compare retrieved atmosphere parameters by different RO (radio occultation) observations, like FORMOSAT-3/COSMIC (Formosa Satellite-3 and Constellation Observing System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…The differences with those estimations could be due to the uncertainties of the PWV radiosonde data and the spatial and temporal separations between GNSS and radiosonde data. Similar results can be found in Ohtani et al [9] (a little higher) or Zhang et al [11] that found a mean RMS of 2.41 mm in a multiple comparison of PWV.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The differences with those estimations could be due to the uncertainties of the PWV radiosonde data and the spatial and temporal separations between GNSS and radiosonde data. Similar results can be found in Ohtani et al [9] (a little higher) or Zhang et al [11] that found a mean RMS of 2.41 mm in a multiple comparison of PWV.…”
Section: Resultssupporting
confidence: 91%
“…The results shows that GPS-retrieved PWV and PWV derived from radiosonde agrees well, with a high correlation coefficient. The correlation coefficients obtained are consistent with the values found in Gui et al [10] and Zhang et al [11]. In general, GNSS-retrieved PWV are overestimated compared with PWV derived from Radiosonde.…”
Section: Resultssupporting
confidence: 90%
“…The third-generation, coarser-resolution reanalyses (ERA-Interim, JRA-55, and NCEP-CFSR) performed slightly worse overall (median KGE of 0.55, 0.52, and 0.52, respectively). ERA-Interim performed slightly better than other third-generation reanalyses, consistent with earlier studies focusing on P (Bromwich et al, 2011;Peña Arancibia et al, 2013;Palerme et al, 2017;Beck et al, 2017c) and other atmospheric variables (Bracegirdle and Marshall, 2012;Jin-Huan et al, 2014;Zhang et al, 2016). All (re)analyses, including the new ERA5-HRES, underestimated the variability (Figs.…”
Section: Evaluation Approachsupporting
confidence: 87%
“…ERA5 can provide global TPW data at a high temporal resolution of 1 hr and a horizontal spatial resolution of 30 km (0.25° × 0.25° in grid). ERA5 is superior compared to widely used ERA‐Interim due to more data sources and new technology in data assimilation system, especially with its higher spatial and temporal resolution (Zhang et al, ). Since it is gap‐free across the whole globe, ERA5 can be adequately collocated to different satellite sampling patterns in space and time to get the satellite‐sampled data sets to construct the sampling errors in satellite data.…”
Section: Methodologies and Datamentioning
confidence: 99%